2013
DOI: 10.1021/am401459c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Plasmonic Ag/AgX-CNTs (X = Cl, Br, I) Nanocomposite Photocatalysts and Synergetic Degradation of Organic Pollutant under Visible Light

Abstract: A series of novel well-defined Ag/AgX (X = Cl, Br, I) loaded carbon nanotubes (CNTs) composite photocatalysts (Ag/AgX-CNTs) were fabricated for the first time via a facile ultrasonic assistant deposition−precipitation method at the room temperature (25 ± 1°C). X-ray diffraction, X-ray photoelectron spectroscopy, nitrogen adsorption−desorption analysis, scanning electron microscopy, and ultraviolet−visible light absorption spectra analysis were used to characterize the structure, morphology, and optical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(64 citation statements)
references
References 47 publications
(89 reference statements)
8
56
0
Order By: Relevance
“…The time required for complete inactivation of 1.5 × 10 7 cfu mL −1 of E. coli was extent to 50 and 60 min by Ag/AgCl-CNTs and Ag/AgI-CNTs, respectively. The order of photocatalytic disinfection activity is consentience with photocatalytic degradation of 2, 4, 6-tribromophenol reported in our previous study [30]. In addition, a study reported that Ag + at high concentration exhibited bactericidal activity [31].…”
Section: Photocatalytic Disinfection Performancementioning
confidence: 54%
See 3 more Smart Citations
“…The time required for complete inactivation of 1.5 × 10 7 cfu mL −1 of E. coli was extent to 50 and 60 min by Ag/AgCl-CNTs and Ag/AgI-CNTs, respectively. The order of photocatalytic disinfection activity is consentience with photocatalytic degradation of 2, 4, 6-tribromophenol reported in our previous study [30]. In addition, a study reported that Ag + at high concentration exhibited bactericidal activity [31].…”
Section: Photocatalytic Disinfection Performancementioning
confidence: 54%
“…The CNTs were pretreated by refluxing in the mixture of concentrated H 2 SO 4 acid (95-98%) and HNO 3 (65-68%), and the Ag/AgX-CNTs photocatalysts were prepared by an ultrasonic assistant deposition-precipitation method according to our previous study [30]. The crystal phase composition, surface chemistry properties as well as surface structure of the photocatalysts before and after used were characterized by X-ray diffraction (XRD, Rigaku Dmax 2200 V X-ray diffractometer), X-ray photoelectron spectroscopy (XPS, S-520/INCA 300 spectrometer using 300 W Mg-K␣ radiation, and the binding energies were referenced to the C1s line at 284.8 eV from adventitious carbon) and the Fourier transform infrared spectroscopy (FTIR, Bruker EQUINOX55 spectrometer).…”
Section: Preparation and Characterization Of Photocatalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…While incorporation of AgX in high specific surface area substrate is another promising strategy in photocatalytic activity promotion, especially in wastewater treatment [322][323][324][325][326]. With the substrates as dispersing templates, homogeneous and uniform semiconductor crystal morphology could be formed, which in turn can enhance their photocatalytic performance [327][328][329][330][331][332][333][334]. The graphene sheets with high optical transmittance, large 2D specific surface area, unique electronic properties and locally conjugated aromatic system has regarded as one kind of ideal substrate candidates for photocatalytic deposition.…”
Section: Other Non-photoactive Materialsmentioning
confidence: 99%